Skrb na področju hendikepa med institucijami in skupostjo - Leskošek, Vesna (Socialno delo, 2015)
Slovene care system in the field of disability is predominantly institutional. Institutional care is legally regulated and financially stable and the same applies also to community services, organised by institutions, like group homes or residential settings. The opposite can be claimed for group homes organised by non-governmental organisations: they are unregulated and poorly financed. There is a lack of quality standards and good practices in the group homes. Care at homes is partly regulated, because the law regulates the work of family carers, but there is a lack of any kind of regulations of personal assistance as the one that assures the most of independency and control over the life of the handicapped by themselves. Care system is based mostly on women's care work and is, in the case of family carer, evidently gender biased. On the one hand, care system expels women from the labour market but, on the other hand, doesn't assure decent pay for care work.
Keywords: institucionalna oskrba; institutional care; community based care services; skupnostna skrb; osebna asistenca; personal assistance; družinski pomočnik; family carer